PENGEMBANGAN PANDUAN PRAKTIKUM LABORATORIUM VIRTUAL PADA MATERI ARUS LISTRIK SEARAH - Kurniati, Kurniati; Suseno, Nyoto; Salim, M. Barkah (Universitas Muhammadiyah Metro, 2020)
Abstract: The rapid development of technology has an influence on the world of education. Physics is one of the subjects that are considered difficult so that the need for supporting activities is practicum activities. Practicum activities can be done using a virtual laboratory. This study aims to develop a virtual laboratory practical guide for direct current electric material in class XII semester 1 at SMA Negeri 4 Metro Tejo Sari, Metro Timur District which is expected to support the physics learning process, especially the subject of series circuits, parallel circuits and Kirchhoff's law. The type of research used is research and development (R&D). The model used is a 4D model developed by Thiagarajan. This model consists of 4 stages, namely define (analyze needs), design (design a product), development (develop the designed product), and finally desseminate (disseminate the product). The instrument used is an assessment questionnaire. There are two types of questionnaires used, the first is a material and media expert validation questionnaire, and the second is a student and teacher response questionnaire. The practical guide used for virtual laboratory practicum activities is made in web format (.html) using Articulate Storyline 3 media. The results of the material and media expert validation test obtained an average percentage value of 84.59% with a very decent category. The practicality of the virtual laboratory practicum guide obtained an average percentage value of 82.05% in the very practical category. This proves that the virtual laboratory practical guide on direct current electric material can be used in learning activities at school. The virtual laboratory practicum guide should be operated using a computer with a fairly stable internet connection.